Host protein PRPS2 interact with the non-structural protein p17 of Avian Reovirus and promote viral replication - Hu Xiaomiao; Zhao Ruihong; Li Wei; Pan Xiaocheng; Dai Yin; Wu Huimin; Wu Yantao; Zhang Chengcheng (Poultry Science)
Avian reovirus (ARV) is highly prevalent in healthy poultry flocks and has been linked to viral arthritis/tendonitis, dwarf syndrome, chronic respiratory disease, and immunosuppression in avian species, resulting in significant economic losses within the poultry industry. The non-structural protein p17 encoded by ARV induces cellular autophagy and facilitates viral proliferation, playing a pivotal role in viral pathogenesis. To further elucidate the pathogenic mechanism basis of ARV p17 protein function, we employed a yeast two-hybrid system to identify Phosphoribosyl pyrophosphate synthetase 2 (PRPS2) as an interacting host protein with p17. In this study, we validated the interaction between PRPS2 and p17 using laser confocal microscopy, coimmunoprecipitation, and GST-Pulldown assays. Moreover, our findings demonstrate that the C-terminal region of PRPS2 is responsible for its binding to the p17 protein. Intriguingly, ARV infection significantly upregulated PRPS2 expression levels. Additionally, PRPS2 was shown to have a substantial impact on ARV replication; overexpression of PRPS2 increased ARV replication while knockdown of PRPS2 resulted in decreased quantities of ARV particles. Furthermore, our findings suggest that this process involves cellular apoptosis as a potential mechanism underlying these observations. Overall, this research provides valuable insights into elucidating the function of the p17 protein and sheds light on the pathogenic mechanism involving ARV-induced cellular apoptosis while offering novel perspectives for exploring therapeutic targets against ARV.